2021
DOI: 10.1038/s41467-021-21825-w
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking peptide and repurposed drugs inhibit both entry pathways of SARS-CoV-2

Abstract: Up to date, effective antivirals have not been widely available for treating COVID-19. In this study, we identify a dual-functional cross-linking peptide 8P9R which can inhibit the two entry pathways (endocytic pathway and TMPRSS2-mediated surface pathway) of SARS-CoV-2 in cells. The endosomal acidification inhibitors (8P9R and chloroquine) can synergistically enhance the activity of arbidol, a spike-ACE2 fusion inhibitor, against SARS-CoV-2 and SARS-CoV in cells. In vivo studies indicate that 8P9R or the comb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 48 publications
1
50
0
Order By: Relevance
“…The 8P9R can inhibit the two entry pathways of SARS-CoV-2 in cells including endocytic pathway and TMPRSS2-mediated surface pathway by aggregating viral particles. In addition, 8P9R, or the combination of repurposed drugs, arbidol, chloroquine and camostat could significantly suppress SARS-CoV-2 replication in hamsters and SARS-CoV in mice 185 .…”
Section: Small-molecule Sars-cov-2 Inhibitors Targeting Host Proteinsmentioning
confidence: 98%
“…The 8P9R can inhibit the two entry pathways of SARS-CoV-2 in cells including endocytic pathway and TMPRSS2-mediated surface pathway by aggregating viral particles. In addition, 8P9R, or the combination of repurposed drugs, arbidol, chloroquine and camostat could significantly suppress SARS-CoV-2 replication in hamsters and SARS-CoV in mice 185 .…”
Section: Small-molecule Sars-cov-2 Inhibitors Targeting Host Proteinsmentioning
confidence: 98%
“…HD5 blocked ACE2 receptors on host cells (214). The cross-linking peptide 8P9R showed potent antiviral activity against SARS-CoV-2 by cross-linking viruses to reduce viral entry on cell surface, and by interfering endosomal acidification to block viral entry through endocytic pathway (215).…”
Section: Peptide Inhibiting Viral Entry and Replicationmentioning
confidence: 99%
“…A study by Ou et al found that the Cathepsin L inhibitor, SID 26681509, independently decreased SARS-CoV-2 S pseudovirion entry by about 76% at 2 μM [ 155 ]. The P9 derivates, P9R and 8P9R, have also shown significant activity against SARS-CoV and SARS-CoV-2 ranging in the low micro- to nanomolar range [ 156 , 157 ]. More importantly, 8P9R demonstrated antiviral activity by decreasing the SARS-CoV-2 viral load in vivo in mice and hamsters [ 157 ].…”
Section: Host Proteases and Endosome Acidification Inhibitorsmentioning
confidence: 99%